2013
DOI: 10.1155/2013/862806
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ethanol Extract ofFructus lyciiand Its Constituents Lutein/Zeaxanthin in Protecting Retinal Pigment Epithelium Cells against Oxidative Stress:In VivoandIn VitroModels of Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) is a major cause of blindness worldwide. Oxidative stress plays a large role in the pathogenesis of AMD. The present study was to evaluate the effects of Fructus lycii ethanol extract on AMD in mice and to investigate whether combination of lutein and zeaxanthin, two carotenoid pigments in Fructus lycii, could protect human retinal pigment epithelial ARPE-19 cells treated with hydrogen peroxide (H2O2) in vitro. We found that severe sediment beneath retinal pigment epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Cathepsin B is a thiol-dependent lysosomal proteinase that can degrade collagens, connective tissue proteins, and certain native enzymes [ 58 ]. Furthermore, the expression of cathepsin B and cystatin C was significantly increased at both gene and protein levels in mice with an experimental model of AMD, which further strengthened the association of these two enzymes with the development of AMD [ 59 ]. Visual cells also secrete cystatin C, resulting in protection of the surface proteins from degradation.…”
Section: The Effects On Amdmentioning
confidence: 96%
See 1 more Smart Citation
“…Cathepsin B is a thiol-dependent lysosomal proteinase that can degrade collagens, connective tissue proteins, and certain native enzymes [ 58 ]. Furthermore, the expression of cathepsin B and cystatin C was significantly increased at both gene and protein levels in mice with an experimental model of AMD, which further strengthened the association of these two enzymes with the development of AMD [ 59 ]. Visual cells also secrete cystatin C, resulting in protection of the surface proteins from degradation.…”
Section: The Effects On Amdmentioning
confidence: 96%
“…In the pathogenesis of AMD, the equilibrium between MMP-2 and TIMP-2 is disrupted, promoting the progression of the disease [ 75 ]. Present data [ 59 ] showed that these two molecules were all upregulated in ARPE-19 cells under oxidative stress. However, L/Z abolished the elevated expression of MMP-2 and TIMP-2 in H 2 O 2 -treated ARPE-19 cells, suggesting that L/Z could be beneficial for oxidative stress-involved AMD by regulating matrix homeostasis.…”
Section: The Effects On Amdmentioning
confidence: 99%
“…Many factors contribute to AMD. One dominant factor is the increasing age of the retina, where the RPE becomes damaged due to a progressively impaired DNA repair system that fails to repair oxidative damage from prolonged exposure to visible light, ultraviolet A and reactive oxygen species (ROS) over time 2 . Cigarette smoking is another factor that contributes to the production of ROS and oxidative damage on the RPE layer.…”
Section: Introductionmentioning
confidence: 99%
“…I cannot judge that effects of LSF result from protection against H2O2-induced cell death or an increased proliferation. 24 h treatment with H2O2 has been shown to cause toxicity in ARPE-19 cells 1 2 . The underlying raw data also demonstrate that the absorbance was reduced from 2.0+ to 1.0+ between CA-H2O2 (fig.1A) and CA+H2O2 (Fig.1b), if comparable.…”
mentioning
confidence: 99%